Dynamic Characteristic and Fatigue Accumulative Damage of a Cross Shield Tunnel Structure under Vibration Load - Qixiang Yan; Hang Chen; Wenyu Chen; Junchen Zhang; Shuqi Ma; Xi Huang (Shock and Vibration)
This study presents an improved constitutive model for concrete under uniaxial cyclic loading which considers the fatigue stiffness degradation, fatigue strength degradation, and fatigue residual strain increment of concrete fatigue damage. According to the constitutive model, the dynamic response and cumulative damage of the tunnel cross structure under various train operation years were analyzed. The results show that the vibration in the middle of the main tunnel is most violent. With the increase of train operation period, the acceleration in the middle of the transverse passage floor, both sides of the wall corner and the vault increase significantly, and the maximum principal stress increases significantly only in both sides of the wall corner. The compressive damage is mainly distributed at both sides of the wall corner, while tensile damage is distributed in both sides of the inner wall corner. The accumulative damage of the cross structure exhibits a two-stage profile. The size and range of accumulative tensile damage of the connecting transverse passage are greater than those of accumulative compressive damage.